Socio-Economic Determinants Shaping Institutional Delivery in Gandaki Province, Nepal - Dahal, Ram Chandra (International Research Journal of MMC, 2025)
Institutional delivery services are crucial for improving maternal and neonatal health. Their utilization is influenced by diverse socio-economic and geographical determinants, as seen in Gandaki Province, Nepal. The study assessed the determinants of institutional delivery using 206 observations drawn from primary sampling unit which has used NDHS, representing different demographics. Age, birth-order, religion, caste/ethnicity, education, residence, and the wealth index were among the factors that were analyzed by employing logistic regression to assess how they actually influenced institutional delivery rates. The results show that within-birth cohort differences were largely in social status, and wealth index considers using institutional delivery services, while younger (20-24 years) women showed lower odds of using institutional delivery (OR = 0.33432, p = 0.046). Access to educational attainment was the most associated factor positively affecting service utilization because women with higher education have significantly higher odds (OR = 12.92771, p = 0.021), thus signifying the incredible transformational effect of education. Socio-economic factors reflective through wealth index show that middle-income and richer households were more likely to use institutional delivery services. The difference among castes/ethnic groups was big, however. Brahmin/Chhetri (OR = 0.269745, p = 0.044) and Janajati women (OR = 0.170093, p = 0.02) were much less likely to deliver in an institution than other groups. While living in a rural area was not statistically significant in the impact, the geographical factor and poor health infrastructure were vital concerns. The study was directed towards the very focus of attending to socio-economic inequalities, quality health care, and the sensitization of institutional deliveries. It stresses the much-needed multi-dimensional approaches-reforms in policy, education, and infrastructure development that will facilitate the access of maternal healthcare into the Gandaki Province. This study also brings some understanding to the helpful for specific involvements aimed at closing gaps between institutional delivery services and maternal and newborn results. Future research necessitates inquiries to assess the effectiveness of these strategies towards achieving equitable access health care across the boundaries of Nepal. The study implies that targeted policy reforms and multi-dimensional strategies addressing socio-economic disparities, educational access, and healthcare infrastructure are essential to improving institutional delivery rates and achieving equitable maternal and neonatal health outcomes in Gandaki Province, Nepal.